Millions of historical monthly rainfall observations taken in the UK and Ireland rescued by citizen scientists. Issue 2 (28th March 2022) - Hawkins, Ed; Burt, Stephen; McCarthy, Mark; Murphy, Conor; Ross, Catherine; Baldock, Mike; Brazier, John; Hersee, Gill; Huntley, Jacqui; Meats, Richard; O'Grady, John; Scrimgeour, Ian; et al.
Abstract: Recovering additional historical weather observations from known archival sources will improve the understanding of how the climate is changing and enable detailed examination of unusual events within the historical record. The UK National Meteorological Archive recently scanned more than 66, 000 paper sheets containing 5.28 million hand‐written monthly rainfall observations taken across the UK and Ireland between 1677 and 1960. Only a small fraction of these observations were previously digitally available for climate scientists to analyse. More than 16, 000 volunteer citizen scientists completed the transcription of these sheets of observations during early 2020 using the RainfallRescue.org website, built using the Zooniverse platform. A total of 3.34 million observations from more than 6000 locations have so far been quality controlled and made openly available. This has increased the total number of monthly rainfall observations that are available for this time period and region by a factor of six. The newly rescued observations will enable longer and much improved reconstructions of past variations in rainfall across the British and Irish Isles, including for periods of significant flooding and drought. Specifically, this data should allow the official gridded monthly rainfall reconstructions for the UK to be extended back to 1836, and even earlier for some regions. Abstract : Recovering additional historical weather observations will enable improved understanding of how the climate is changing and unusual weather events. More than 16, 000 volunteer citizen scientists completed the transcription of millions of monthly rainfall observations taken in the UK and Ireland between 1677 and 1960. A total of 3.34 million observations from more than 6000 locations have now been quality controlled and made openly available, increasing the total number of monthly rainfall observations that are available by a factor of six.